Bulk Segregant Analysis Technique to Target Seasonality and Runnering Loci in Diploid Strawberries - Cetin Cekic (Journal of New Results in Science)
Bulked segregant analysis was used to determine inter-simple sequence repeat DNA (ISSR) markers for two genes, one controls seasonality and other runnering in diploid Fragaria spp. ISSR- PCR analysis was performed using these DNA pools as template. The bulks are screened for differences using anchored simple sequence polymorphic DNA primers which generates clean band profiles and polymorphic fragments were detected. Using 23 primers, either singly or pairwise, we established 16 markers tightly linked to the seasonality locus and 7 markers for runnering locus. This bulked segregant method can be applied for any species and any region of interest in which detailed linkage maps or physical maps are needed.